Нова верхньопалеолітична стоянка Оболоння в Середньому Подесенні - Ступак, Д.В. (Кам’яна доба України, 2010)
У статті висвітлюються матеріали нової епіграветської стоянки у Середньому Подесенні Оболоння. Головну увагу приділено опису бивня з гравійованими зображеннями, який за специфікою зображень є найближчою аналогією відомому бивню з Кирилівської стоянки. In 2010 year in Middle Desna region was discovered new Epigravettian site Obolonnya. This site is the most southern located site in the Middle Desna area. On this site was founded engraved mammoth tusk. At this tusk are elements of images that connect it with Mezin site, and present are those who associate it with Kirilovska site. According to the style of the image, this tusk is more the closest analogy of engraved mammoth tusk from Kirilovska site. In flint complex of this site present blade made from import kanivsky flint from Middle Dnipro region. Thus, at this site is very promising for further research. And this site is very promising for the study of intercultural contacts of Epigravettian time in Dnipro basin region.